La helicicultura en Colombia : reforma normativa y rezago productivo - López Palechor, Leydy Evonne; Ruano Ibarra, Elizabeth del Socorro; Vinicius Brisola, Marlon (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Páginas 225-250